Pengaruh Metode Pembelajaran Kooperatif dan Penguasaan Kosakata Terhadap Pemahanam Bacaan Bahasa Inggris - Hilal Fathoni (INFERENCE: Journal of English Language Teaching, 2020)
This study uses an experimental method, namely by giving different treatments to two student learning groups. The population in this study were private Madrasah Aliyah students in the district. Karawang in the 2019/2020 academic year totaling ?500 students. The results there are 1). There is a significant influence of cooperative learning methods on the English reading comprehension of private Madrasah Aliyah students in the district. Karawang. This is evidenced by the sig value of 0,000 <0.05, with Fcount = 15.638. 2). There is a significant influence in the mastery of vocabulary on the understanding of English reading of Madrasah Aliyah Private students in the district. Karawang. This evidenced by the sig value of 0.047 <0.05, with Fcount = 4.058. 3). There is a significant interactive influence on cooperative learning methods and vocabulary mastery of English students’ reading comprehension of Madrasah Aliyah Private in the district. Karawang. This is evidenced by the sig value of 0.016 <0.05, with Fcount = 6.062. The use of cooperative learning methods and the use of vocabulary can influence students’ higher comprehension of English reading.